Sex-specific colony attendance before and during the fertilization window in Nazca boobies - Ursillo, Trey; Reyes, David; Reyes, Enzo M. R.; van Oordt, Francis; Morán, Andreinna; McKee, Jennifer L.; Rebol, Erynn J.; London, Mary Grace; Huskey, Jessica B.; Anderson, David J. (Frontiers in Bird Science, 2026)
Nazca boobies (Sula granti), a colonial pelagic seabird, face a tradeoff before egg production between foraging at sea and mating effort on land. All individuals must both forage and secure a partner for the coming breeding season. However, the sex ratio is male-biased, so males must attend the colony to attract females (the limiting sex) and counter females’ conspicuous sexual promiscuity. We hypothesized that this exacerbates the sea-land tradeoff for males, rewarding colony attendance at the expense of foraging opportunities. We tested the prediction that males attend the colony more than females do early in breeding. Four years of nocturnal attendance data supported the prediction: males did consistently attend the colony more than females before and during egg-laying, reducing the males’ time at sea accordingly for weeks. This difference nearly disappeared after the clutch was complete and pair bonds firmly established. The exception to this pattern was notable: on the night before clutches were initiated the attendance probability of males in these breeding pairs was anomalously low (0.18), most males being at sea. Before and after this night these breeding males had attendance probabilities of 0.69 and 0.71, respectively. This night in each breeding pair’s timeline separates the fertilization windows of the first egg and a possible second (and final) egg, presenting a brief break in paternity risk for the males, and most go to sea. These results are consistent with a sexually selected response by males to improve success in pairing and paternity, and suggest a tradeoff with foraging.